2021
DOI: 10.1111/tbj.14125
|View full text |Cite
|
Sign up to set email alerts
|

Response in breast vs axilla after neoadjuvant treatment and implications for nonoperative management of invasive breast cancer

Abstract: Improved imaging and neoadjuvant chemotherapy (NAT) have led to higher pathologic complete response rates (pCR) in patients with invasive breast cancer. This has questioned the necessity of surgery and axillary lymph node (ALN) dissection in these patients. Prospective clinical trials are implementing extensive core biopsies of the tumor bed of patients with clinical complete response as a means to identify and spare them breast surgery. In addition, it is anticipated that patients with pCR are most likely goi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…We also observed that the axillary pCR rate varied with the breast MP grade. However, axillary pCR is only a moderate predictor of breast pCR (3,5,12). Therefore, the extent of axillary response and ypN stage may play different roles in predicting prognosis and guiding treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also observed that the axillary pCR rate varied with the breast MP grade. However, axillary pCR is only a moderate predictor of breast pCR (3,5,12). Therefore, the extent of axillary response and ypN stage may play different roles in predicting prognosis and guiding treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis indicates that Ki67 10-20%+ patients may be the most axillary responsive group. Hank Schmidt et al (3). and Diego Flores-Funes et al ( 14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathological evaluation of post-NAC samples remains the gold standard for assessing tumor response to neoadjuvant treatments. It is extremely important to determine the degree of pathological response, which may differ between the primary tumor and the axillary lymph node metastases, and to evaluate the histological and biological characteristics of the residual tumor in both the breast and the axilla [ 56 , 57 ]. Pathologists have adopted a different approach for the macroscopic assessment, extent of sampling, and microscopic analyses of post-NAC surgical samples.…”
Section: Pathological Evaluation Of Residual Diseasementioning
confidence: 99%
“…After NAT, approximately 40% of patients with breast cancer achieve a pathological complete response (pCR), best defined as the absence of invasive carcinoma cells both in the breast and in the examined ALN [ 11 ]. It should be noted that the degree of response may vary between the primary tumor and the ALN metastases, and among the metastases themselves [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%